Juvenile Justice Criminal Law Policy Between Indonesia and Malaysia: A Comparison - Farhan Taufiqurahman; Handar Subhandi Bakhtiar (Ius Comparatum: Journal of Law Studies, 2025)
This paper aims to compare the criminal law policies of juvenile justice in Indonesia and Malaysia. Child protection is an essential aspect of social development and community welfare. In this context, a comparison between the two countries offers valuable insights into the approaches, policies, and implementations of child protection. The results of the study show that both countries have made serious efforts to protect children's rights. However, there are differences in the legal approach and implementation of child protection policies. In Indonesia, regulations governing child protection exist, such as Law Number 23 of 2002 concerning Child Protection. In Malaysia, the Children's Law of 2001 regulates children's rights. Both countries have their own characteristics in dealing with children in conflict with the law, both in terms of legal basis, institutions, and settlement approaches. This study employs a normative juridical method, incorporating a statutory and comparative legal approach. The results of the study indicate that Indonesia has progressive regulations in place through the SPPA Law, but still faces challenges in their implementation. Meanwhile, Malaysia still applies a relatively conservative and institutional approach.